Optimizing T Cell-Based Therapy for Glioblastoma - Karachi, Aida; Dastmalchi, Farhad; Nazarian, Saina; Huang, Jianping; Sayour, Elias J.; Jin, Linchun; Yang, Changlin; Mitchell, Duane A.; Rahman, Maryam (Frontiers in Immunology, 2021)
Evading T cell surveillance is a hallmark of cancer. Patients with solid tissue malignancy, such as glioblastoma (GBM), have multiple forms of immune dysfunction, including defective T cell function. T cell dysfunction is exacerbated by standard treatment strategies such as steroids, chemotherapy, and radiation. Reinvigoration of T cell responses can be achieved by utilizing adoptively transferred T cells, including CAR T cells. However, these cells are at risk for depletion and dysfunction as well. This review will discuss adoptive T cell transfer strategies and methods to avoid T cell dysfunction for the treatment of brain cancer.